What Do We Know About Campus Sexual Violence? A Content Analysis of 10 Years of Research - Linder, Chris; Grimes, Niah; Williams, Brittany M; Lacy, Marvette C; Parker, Brean'a (Review of higher education, 2020)
We examined 10 years of scholarship about campus sexual violence from 12 social sciences databases to illuminate the trends, gaps, and possibilities in research. Using a content analysis methodology, we examined 540 articles. In this paper, we highlight the methodologies, subjects, and demographics of participants in the studies. We use a power-conscious framework to interpret our findings, which indicate that campus sexual violence research primarily focuses on white, transgender, heterosexual college women as victims of sexual violence. Further, most scholarship focuses on victims, rather than perpetrators of sexual violence, leaving significant gaps in effectively eradicating campus sexual violence.